ChemInform Abstract: Catalytic Asymmetric α‐Amination of α‐Branched Ketones via Enol Catalysis. Issue 43 (October 2015) - Shevchenko, Grigory A.; Pupo, Gabriele; List, Benjamin
Abstract A chiral anthracenylbinaphthyl‐derived phosphoric acid catalyzes the title reaction in a regio‐ and enantioselective manner.